Comparative efficacy and safety of different SGLT2 inhibitor-based combination strategies in HFrEF: a systematic review and network meta-analysis - Jiang, Neng; Zhang, Yuling; Tang, Yue; Tan, Hongmei (Frontiers in Endocrinology, 2026)
BackgroundThe optimal combination therapy for heart failure with reduced ejection fraction (HFrEF) involving sodium-glucose transporter 2 inhibitors (SGLT2i), angiotensin receptor–neprilysin inhibitors (ARNI), and conventional triple therapy remains uncertain due to the lack of direct comparative evidence.MethodsWe conducted a Bayesian network meta-analysis of randomized controlled trials (RCTs) comparing six treatment regimens. Primary outcome was the composite of cardiovascular death and hospitalization. Secondary outcomes included all-cause mortality, Kansas City Cardiomyopathy Questionnaire (KCCQ) scores, 6-minute walk distance (6MWD), N-terminal pro-B-type natriuretic peptide (NT-proBNP) levels, and adverse events (hypotension, hyperkalemia, renal events). All analyses were performed under a Bayesian statistical framework, and the relative efficacy and safety of the six regimens were ranked using surface under the cumulative ranking curve (SUCRA) probabilities.ResultsA total of 22 studies (21 RCTs) involving 24,499 patients were included. For the primary composite outcome, Sotagliflozin-based quadruple therapy ranked first (SUCRA: 90.8%; OR: 0.49, 95%CI: 0.16 to 1.47). Dapagliflozin+triple therapy (SUCRA: 76.8%; OR: 0.83, 95%CI: 0.69 to 0.98) and ARNI+BB+MRA (SUCRA: 76.6%; OR: 0.83, 95%CI: 0.75 to 0.92) demonstrated significant reductions in all-cause mortality. ARNI-based triple therapy was associated with a significantly increased risk of hypotension (OR: 1.67, 95%CI: 1.48 to 1.90), whereas Dapagliflozin and Empagliflozin showed protective effects against renal adverse events. No regimen significantly increased hyperkalemia risk. Additionally, a statistically significant interaction was observed between treatment effects and baseline diabetes burden for the primary outcome (p = 0.003).ConclusionsThis network meta-analysis demonstrates that while all quadruple therapy regimens improve outcomes in HFrEF, important distinctions exist. Sotagliflozin-based therapy may offer advantages in preventing hospitalizations, whereas Dapagliflozin and ARNI are comparable for mortality reduction. The safety profiles differ significantly, particularly regarding hypotension risk with ARNI and renal protection with SGLT2i. The choice of regimen should be individualized based on patient priorities, comorbidities, and safety tolerability profiles.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251112344, identifier CRD420251112344.